IMPLEMENTASI KEPUTUSAN MENTERI KESEHATAN NOMOR HK.01.07/MENKES/33/2025 TENTANG PETUNJUK TEKNIS PEMERIKSAAN KESEHATAN GRATIS DI PUSKESMAS KANIGARAN KOTA PROBOLINGGO - Raisa Aprilia; supriyanto Supriyanto; Mastina Maksin (The Indonesian Journal of Public Administration (IJPA), 2026)
This study examines the implementation of the Free Birthday Health Examination (PKG) program regulated by Decree of the Minister of Health Number HK.01.07/MENKES/33/2025 at Puskesmas Kanigaran, Probolinggo City. This program is a national policy to promote early detection of non-communicable diseases (NCDs). Analysis uses Grindle's (2018) implementation theory through two dimensions: content of policy and context of implementation. The study employs descriptive qualitative methods through in-depth interviews, observation, and documentation. Results show the PKG program at Puskesmas Kanigaran is running adequately. Direct benefits in the form of free and easily accessible health services have successfully encouraged community participation. Detection of suspected tuberculosis even reached 100 percent. However, limited human resources remain the most critical structural constraint. Puskesmas Kanigaran carries the largest target population in Probolinggo City (approximately 23,000 people) with a very limited number of health workers. Actor dynamics are conducive, the institution demonstrates good adaptive capacity through outreach strategies, and implementer compliance and responsiveness are relatively high.